Stepping Towards Sustainable Leadership: Analysis of Leadership Practices In The Mining Industry In Supporting The Achievement of Sustainable Development Goals - Wijaya, Sumadi; Pratomo, Luki Adiati (Asian Journal of Social and Humanities, 2024)
This research aims to fill the research gap by analyzing sustainable leadership practices in the mining industry, expanding the understanding from previous sustainable leadership literature. The focus is to provide a deep understanding of the role of sustainable leadership in supporting the Sustainable Development Goals (SDGs). Qualitative methods are employed to comprehend social phenomena through the collection and analysis of descriptive and non-numeric data. The study explores "Sustainable Leadership Practices at PT ABC and PT XYZ in Supporting the Achievement of Sustainable Development Goals." The findings indicate that PT ABC and PT XYZ implement sustainable leadership practices, including commitments to social, economic, and environmental aspects. However, they face challenges such as resource constraints and organizational cultural changes. Leaders in both companies play a crucial role in communicating the importance of sustainability and leading change. Managerial implications involve developing internal policies that strengthen sustainable leadership practices and enhancing employee awareness. Management needs to address financial and cultural challenges while ensuring compliance with regulations. Investor implications include a deeper understanding of the company's commitment to social, economic, and environmental aspects as an evaluation factor for long-term sustainability.